The Benefits of a Normal Childbirth Care Calendar for Increasing the Application of Childbirth Care Standards by Midwives to Independent Practice in Badung Regency, Bali in 2018 - Budiani Ni Nyoman Budiani (Ikatan Bidan Indonesia (IBI), 2019)
The critical period of a woman during her reproductive period is experienced during labor. Every mother giving birth has the right to get standard maternity care so that the delivery process is safe, the mother and baby are healthy. This study aims to prove that the Normal Childbirth Care calendar can increase the application of standards of childbirth care by midwives in independent practice. Method: Pre-experimental, using the one group pretest-posttest design approach. The subjects of this study were independent practice midwives, a maximum age of 65 years, a minimum work period of 2 years, minimum D3 midwifery graduates. Sample size was 20 people, by proportionate simple random sampling. Data analysis using the Wilcoxon test. Results: the score of applying the standard of delivery care by midwives in independent practice before treatment was found to be the lowest 23, the highest was 36, and the median was 30. After treatment was found the lowest score was 36, the highest was 38, and the median was 38. achieve ideal score (38). There was a significant difference in the application of labor standards before with after being given a normal delivery care calendar (z -3.888; p 0.000). Conclusion: a normal birth care calendar is beneficial in increasing the application of midwife care standards to independent practice.